KECERDASAN SPIRITUAL SEBAGAI INDIKATOR PENGUKURAN KEBERHASILAN PELAKSANAAN PENDIDIKAN KARAKTER - Luh Kadek Dwi Utami (Guna Widya: Jurnal Pendidikan Hindu, 2018)
Character education that is being intensively carried out in Indonesia is felt still not maximal. This should be the main priority that must be completed by all components of education. The educational component requires a valid and relia- ble measuring tool to measure the success rate of character education. The most closely approximated measuring instrument is spiritual intelligence. This is be- cause the indicators and measurement instruments between character education with spiritual intelligence alike. Measuring the level of character education suc- cess can be done by comparing the level of spiritual intelligence of learners be- fore and after the character education. It is the result that becomes the judgment that the character education carried out has been successful, fixed or even failed.